2007
DOI: 10.1590/s1413-70542007000100027
|View full text |Cite
|
Sign up to set email alerts
|

Uso de películas de fécula de mandioca e pvc na conservação pós-colheita de pimentão

Abstract: RESUMOOs produtos hortícolas apresentam vida útil pós-colheita limitada, devido às reações bioquímicas de natureza catabólica, que aumentam com a senescência, causando a morte dos tecidos. Avaliou-se o uso de películas de fécula de mandioca e PVC na manutenção da qualidade pós-colheita de pimentões (Capsicum annuum L.) armazenados em condições ambiente. Pimentões cv. Ikeda foram submetidos a 4 tratamentos: PVC, biofilmes nas concentrações de 3,5%, 4% e 4,5% de fécula de mandioca. Como testemunha foram utilizad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
16

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 6 publications
3
7
0
16
Order By: Relevance
“…This analysis revealed that the mass loss of pepper fruits follows a positive linear equation with the postharvest days ( Figure 1A). These results are in agreement with another report, which showed that the mass loss is explained by a linear equation (Hojo et al, 2007). Similar behavior was also observed for fruit respiration, even though in this case the equation was negative ( Figure 1B).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This analysis revealed that the mass loss of pepper fruits follows a positive linear equation with the postharvest days ( Figure 1A). These results are in agreement with another report, which showed that the mass loss is explained by a linear equation (Hojo et al, 2007). Similar behavior was also observed for fruit respiration, even though in this case the equation was negative ( Figure 1B).…”
Section: Resultssupporting
confidence: 93%
“…Pepper fruits have been used as condiment, either for in natura consumption or as part of industrialized products. Because of the elevated quality losses (Hojo et al, 2007), the commercialization of pepper fruits in natura must proceed immediately after harvest. Thus, the high perishability of pepper fruits makes it relevant to research new techniques for the storage of this product.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31] stored "Pedro Sato" guavas at 25 + 1°C and 85 ± 5% RH and reported that the peel color changed from green to yellow. [28] also observed this same behavior during storage period for peppers coated with cassava starch. Fruit firmness decreased over storage for all the treatments (Fig.…”
Section: Treatmentssupporting
confidence: 66%
“…[14] also observed an increase of +b* values in tomatoes coated with pectin during storage. According to [28], this increase in yellow coloration may associated to changes in L* and -a* values.…”
Section: Treatmentsmentioning
confidence: 99%